Peran Sustainability report, Profitabilitas, Ukuran Perusahaan Pada Nilai Perusahaan: Sektor Infrastruktur, Transportasi dan Logistik - Ahmad Wahyudi; Sari Andayani (Politeknik Ganesha Medan, 2026)
The Indonesian capital market has experienced significant growth in recent years, playing a crucial role in supporting the national economy by serving as a platform for investment and capital raising. This study aims to examine the effects of sustainability reporting, profitability (Return on Assets/ROA), and firm size on firm value, measured by Tobin’s Q, among infrastructure, transportation, and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. A quantitative approach was employed using secondary data obtained from sustainability reports and annual financial statements. The sample was selected through purposive sampling, resulting in 63 observations. Data were analyzed using multiple linear regression with IBM SPSS Statistics version 27. The findings reveal that sustainability reporting and profitability (ROA) have a significant positive effect on firm value, indicating that both non-financial and financial information serve as positive signals that enhance investor confidence and improve corporate prospects. In contrast, firm size has a significant negative effect on firm value, suggesting that larger firms may face greater operational complexity and higher risks, which can reduce investor valuation. Overall, these findings support signaling theory, emphasizing the importance of transparent financial and non-financial disclosures in enhancing firm value.